Longmire. The complete first season [videorecording (DVD)]. - Taylor, Robert; Phillips, Lou Diamond, 1962-; Sackhoff, Katee; Johnson, Craig, 1961- (Warner Home Video, 2013)
To close murder cases under open skies, he's your man. Out of bestselling author Craig Johnson's mystery novels strides Walt Longmire, the charismatic and unflappable sheriff of Absaroka County and the world-weary yet dedicated lead character of this spellbinding hit series.